Feedback : Green and keen. (14th October 2019) - Shepherd, Ben; Bainbridge, Alex; Clarke, Jim; Huber, Michael
Abstract: In reply to Benjamin Skuse's feature article "Leading by example: going green in the lab" (June pp27—30) and Matin Durrani's related editorial "Making physics greener" (June p15), which both discuss how science labs can become greener and cut waste.